STAGES OF FORMATION OF TAX ADMINISTRATION FOR LARGE TAXPAYERS IN UZBEKISTAN (International Conference on Modern Science and Scientific Studies, 2025)
This article analyzes the foreign experience of implementing the tax administration of large taxpayers, as a result of this analysis, issues of improving the tax legislation of the Republic of Uzbekistan, a proposal for further improvement of the tax administration of large taxpayers and recommendations are developed.